Strategi Membangun Komitmen Organisasi Dakwah pada Tahap Merintis: Studi Organisasi Dakwah Nabi di Mekkah - Mawasti, Wahanani (STID Al Hadid Surabaya, 2024)
Considering that the role of organizational commitment is very important for da'wah organizations to develop and be sustainable, efforts are needed to build commitment in the human resources of da'wah organizations. However, so far academic studies on the aspect of building organizational commitment in missionary organizations are still very limited. Previous literature has investigated factors in building organizational commitment to industry. The aim of this study is to explore the strategies of missionary organizations in building member commitment, through a literature review of the strategies used by the prophet Muhammad in building organizational commitment to human resources, especially during the prophet's preaching in Mecca. The method used is a qualitative library study. The results of the study concluded that the Prophet Muhammad's efforts to build the commitment of member organizations in Mecca were in several ways, namely: internalizing the vision of monotheism, consistent and sustainable awareness-based development, creating a positive climate based on human values, and leading by example. The Prophet Muhammad's strategy in building organizational commitment in Mecca can be an inspiration for da'wah organizations in the pioneering phase.